Highly Chemoselective Iridium Photoredox and Nickel Catalysis for the Cross‐Coupling of Primary Aryl Amines with Aryl Halides. Issue 42 (6th October 2016) - Oderinde, Martins S.; Jones, Natalie H.; Juneau, Antoine; Frenette, Mathieu; Aquila, Brian; Tentarelli, Sharon; Robbins, Daniel W.; Johannes, Jeffrey W.
Abstract: A visible‐light‐promoted iridium photoredox and nickel dual‐catalyzed cross‐coupling procedure for the formation C−N bonds has been developed. With this method, various aryl amines were chemoselectively cross‐coupled with electronically and sterically diverse aryl iodides and bromides to forge the corresponding C−N bonds, which are of high interest to the pharmaceutical industries. Aryl iodides were found to be a more efficient electrophilic coupling partner. The coupling reactions were carried out at room temperature without the rigorous exclusion of molecular oxygen, thus making this newly developed Ir‐photoredox/Ni dual‐catalyzed procedure very mild and operationally simple. Abstract : Lights, metal, action : A visible‐light‐promoted dual‐catalytic cross‐coupling procedure combining Ir photoredox catalysis and Ni catalysis to form C−N bonds has been developed. This mild and operationally simple method proceeds at room temperature without rigorous exclusion of O2 and was employed for the cross‐coupling of various aryl amines with electronically and sterically diverse aryl iodides and bromides.